Time-resolved studies of low-temperature, EUV-induced plasmas: EUV emission in selected spectral ranges. (20th December 2019) - Bartnik, A.; Fiedorowicz, H.; Wachulak, P.; Fok, T.
Abstract: Interaction of extreme ultraviolet (EUV) pulses of high intensity with gases results in the creation of non-thermalized plasmas. Energies of the driving photons and photoelectrons are sufficient for creation of excited states, followed by emission of the EUV photons. In most cases, decay times of these states are short comparing to the driving EUV pulse. It means that just after stopping of the driving pulse, the EUV emission corresponding to the excited states should also stop. From our earlier measurements in the optical range, however, it can be concluded that lifetimes of such plasmas exceed a time duration of the driving pulse even two orders of magnitude. Hence, it can be expected that the time duration of the EUV emission can be also significantly longer than the irradiation time. In this work, EUV-induced, low-temperature helium (He), krypton, and xenon plasmas were investigated. EUV emission from these plasmas was studied, using a specially prepared detection system, allowing for time-resolved measurements, in selected spectral ranges. The detection system was based on a paraboloidal collector and a semiconductor photodiode, sensitive for the EUV photons. For spectral selection, the corresponding filters or multilayer mirrors were employed. In most cases, the time duration of the EUV emission was significantly longer than the driving EUV pulse. In case of He plasmas, the emission corresponding to excited atoms was detected even hundreds of nanoseconds after the irradiation. It was also shown that the corresponding time profiles depended on densities of gases to be ionized.